Analisis Kebijakan Pengelolaan Pendidikan di Madrasah Tsanawiyah Darussaadah Kabupaten Lebak - Mumu Zainal Mutaqin; Sanusi Sanusi; Solihin Solihin; Muhammad Arifin; Saepul Bahri (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2022)
This study aims to explore. This study aims to explore management standards in Madrasahs as an effort to realize quality madrasas in the future. And to answer the challenges of madrasas and their implementation, namely the management of learning in madrasas, the principles of management in madrasas. And the problems faced in madrasas and their solutions. This study uses a qualitative method with a descriptive approach, namely research that aims to describe the integrity of a problem or problem that exists in Madrasah Tsnawiyah Darussaadah Cimarga. This qualitative approach can be viewed as a research procedure that produces descriptive data in the form of written or spoken words from people involved in education who can be met, observed, or asked for information. Data collection techniques are observation, interviews and documentation. Implementation of its policies through educational planning that provides clarity of direction in the business process of providing education, so that the management of educational institutions will be carried out more effectively and efficiently. In addition, its implementation covers all areas of school operational implementation, including guidelines, madrasa organizational structure, learning activities as well as community roles and school partnerships. Furthermore, Supervision as a process of monitoring activities which is an activity to correct and correct deficiencies that occur in the process of implementing Madrasah activities. the effort as a methodological combination of data with an emphasis on the objectives that have been set.